A sensitive TAS-ELISA for the detection of some West African isolates of yam mosaic virus in Dioscorea spp. - Njukeng, A.P.; Ariri, G.I.; Hughes, Jacqueline d'Arros; Agindoran, B.O.; Mignouna, Hodeba D.; Thottappilly, G. (2002)
A Nigerian isolate of Yam mosaic virus (YMV), genus Potyvirus from Dioscorea rotundata leaves was used to mechanically inoculate Nicotiana benthamiana (propagation host) plants from which the virus was purified. A hybridoma cell line secreting a monoclonal antibody (Mab) against YMV was produced by fusion of FOX-NY myeloma cells with immune splenocytes from in vivo immunizations of a Balb/C mouse. The polyclonal antiserum to YMV and the Mab (YMV-M24) were used in developing a triple antibody sandwich (TAS) enzyme-linked immunosorbent assay (ELISA) system for the detection of YMV from samples collected from fields. The test gave a positive reaction even at a sap dilution of 1:6250-1:31250 from leaf samples collected from different plants species, while antigen-coated plant (ACP) ELISA using the Mab could detect only to a dilution of 1:1250. TAS-ELISA was more sensitive and reliable when compared with ACP-ELISA using YMV-M24. YMV-M24 detected YMV isolates in some Dioscorea species from seven countries in the main yam growing area of West Africa.